A Pedagogia Histórico-Crítica, a formação de professores e o Programa de Desenvolvimento Educacional do Estado do Paraná: entre avanços e recuos - Gimenes, Lucivani Delmarco (2022)
The Critical-Historical Pedagogy, institutionalized in 1990 in Paraná through the Basic Curriculum for Public School of the State of Paraná, has been an important pedagogical theory in the state, a symbol of struggles and achievements. In this trajectory, Critical-Historical Pedagogy and public education have suffered constant attacks by successive governments. However, in a context of opposition to the ultraliberal measures implemented during Jaime Lerner's administration (1995-2003), the Paraná State Education Development Program was instituted. As part of the training activities of the Education Development Program/PR, the students were supposed to produce scientific productions. Because of this, we decided to analyze these works to define to what extent the Critical-Historical Pedagogy was incorporated and appropriated in these productions and understand the concrete conditions of implementation of this pedagogy in the public schools of the state, under the Education Development Program, between 2007 and 2018. This is bibliographic and documentary research, with a mixed approach (quanti-qualitative). After reviewing the literature pertinent to the object of the research, as well as analyzing the Program's Guiding Documents, we collected data from the Synopses Notebooks of the productions of eight editions of the Education Development Program/PR, covering the 17 Study Lines of the Program, based on a survey using key terms alluding to the Critical-Historical Pedagogy. We also collected data in the Education Development Program Textbooks - Volume I (Scientific Articles), through an informative reading of 38 works previously selected by inclusion and exclusion criteria. In the Synopsis Notebooks, we found a low occurrence of the key terms linked to the Critical-Historical Pedagogy, precisely in 539 abstracts, representing only 1.83% in the total of 29,399 papers constructed and published between 2007 and 2018. These data indicate that, in the investigated period, the thematic incorporation of Critical-Historical Pedagogy in the production of the Education Development Program/PR was little expressive. Concerning the appropriation of the critical-historical conception in the analyzed articles, we found theoretical coherence, however, at an incipient level. We consider that the results found in the combined research reflect the conditions in which pedagogical work and teacher training are developed in the context of a capitalist society in which the school and the State are inserted. About the determinants, we highlight aspects extrinsic and intrinsic to the operationalization of the Program, such as (i) the neopragmatism approach adopted by the National Curricular Guidelines for teacher training post-Law of Education Guidelines and Bases No. 9.394/96, which, grounded in the epistemology of practice, configure a formative model based on competencies by the adaptive bias; and (ii) the heterogeneity of the State Department of Education in the construction of the state's pedagogical proposal, which, in the period from 2007 to 2018, is expressed in the multifaceted trend of the Curricular Guidelines for the State of Paraná, elaborated and implemented during the Roberto Requião Government (2003-2010), and in the resumption of the pedagogy of competencies because of the "Management for x Results", from the Beto Richa Government (2011-2018). In our understanding, these implications limited the conditions conducive to the appropriation and theoretical practical incorporation of the Critical-Historical Pedagogy through the Education Development Program/PR.